Analisis Implementasi Kebijakan Harga Minimum Industri Rokok di Indonesia - Arifin, Khomsun; Ahsan, Abdillah; Yuniar, Adela Miranti (UI Scholars Hub, 2023)
Large companies have the financial power to play a price strategy so it can threaten the existence of small companies. In this case, the government implements a minimum price policy to protect small entrepreneurs from unfair price competition. This paper aims to determine the correlation between implementing the minimum price policy and the price strategy in the cigarette industry. Using panel data of DJBC market transaction price survey for 2015-2019 period covering 199 cigarette brands in 25 Indonesian provinces and random effect model, the study found that the implementation of the minimum price policy (HTP 85%) is significantly correlated with price strategy.